Pattern of antibiotic sensitivity and resistance of uropathogenes among pediatric patients with urinary tract infection - Ghayth M. AbdulRazzaq (University of Mosul, 2013)
Objectives: studying the microbiological profile by isolation of the types of bacteria that are most frequently causing UTI in pediatric patients and assessing the antibiotic resistance profile of 10 different antibiotics that are used for treatment of such infection. . Methods: Urine samples from 900 symptomatic UTI cases attending Ibn Alatheer Teaching Hospital from May 2010 to September2011 were collected . Urinary isolates were identified by conventional methods and antibiotic resistance testing was performed by Kirby Bauer's disc diffusion method. Results: We identify 6 species of uropathogens responsible for UTI in pediatric patients . Females are more susceptible to the UTI than males, however they usually infected by the same bacterial species. E. coli is the most predominant uropathogen in pediatric UTI. The isolated uropathogenes showed a heavy resistance pattern toward many antibiotics like Cotrimoxazole (84.1%) Amoxicilline(72.6%), Nalidixi acid(57.4%). Cephalosporin (particularly cefotaxime) , Augmentin, gentamycine and nitrofurantoin exhibit adequate antibiotic activity against uropathogens while Ciprofloxacin and Amikacine subjected to the least resistant pattern of commonly used antibiotics. Conclusion: E. coli is still the most common type of bacteria causing UTI in male and female pediatric patients. Pediatric urine culture isolates are becoming increasingly resistant to commonly used antibiotics. Empirical treatment with Cotrimoxazole, Amoxicillin, or Nalidixic acid as initial drug is relatively ineffective. Cefotaxim and gentamycin can be considered as effective line for treatment of UTI . Amikacine and Ciprofloxacine are less likely to be subjected to drug resistance.